Carbapenem Resistance in Elizabethkingia meningoseptica Is Mediated by Metallo-β-Lactamase BlaB - Gonzalez, Lisandro Javier (2012)
Elizabethkingia meningoseptica, a Gram-negative rod widely distributed in the environment, is resistant to most beta-lactam antibiotics. Three bla genes have been identified in E. meningoseptica, coding for the extended-spectrum serine-beta-lactamase CME (class D) and two unrelated wide-spectrum metallo-beta-lactamases, BlaB (subclass B1) and GOB (subclass B3). E. meningoseptica is singular in being the only reported microorganism possessing two chromosomally encoded MBL genes. Real-time PCR and biochemical analysis demonstrate that the three bla genes are actively expressed in vivo as functional beta-lactamases. However, while CME elicits cephalosporin resistance, BlaB is the only beta-lactamase responsible for E. meningoseptica resistance to imipenem, as GOB activity is masked by higher cellular levels of BlaB. On the other hand, we demonstrate that bla(BlaB) expression is higher in the stationary phase or under conditions that mimic the nutrient-limiting cerebrospinal fluid colonized by E. meningoseptica in human meningitis.